2021
DOI: 10.3389/ffgc.2021.780299
|View full text |Cite
|
Sign up to set email alerts
|

Successional and Intraspecific Variations in Leaf Traits, Spectral Reflectance Indices and Herbivory in a Brazilian Tropical Dry Forest

Abstract: Leaf traits are good indicators of ecosystem functioning and can affect herbivory and leaf reflectance patterns, allowing a better understanding of changes in environmental conditions, such those observed during forest natural regeneration. The aim of this study was to evaluate the intraspecific variation in leaf traits and their influence on the pattern of herbivory and leaf reflectance in three species distributed along a successional gradient (early, intermediate and late stages) in a tropical dry forest (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…In fact, a growing number of studies have shown that there is no clear relationship between insect herbivory and leaf traits (Alves et al 2021;Moreira et al 2019;Salminen & Karonen 2011), implying that leaf traits should be used with caution when predicting insect herbivory under field conditions. Thus, why do leaf traits that indicate leaf quality often have ambiguous effects on insect herbivory?…”
Section: Predictors Insect Herbivorymentioning
confidence: 99%
“…In fact, a growing number of studies have shown that there is no clear relationship between insect herbivory and leaf traits (Alves et al 2021;Moreira et al 2019;Salminen & Karonen 2011), implying that leaf traits should be used with caution when predicting insect herbivory under field conditions. Thus, why do leaf traits that indicate leaf quality often have ambiguous effects on insect herbivory?…”
Section: Predictors Insect Herbivorymentioning
confidence: 99%